2015
DOI: 10.1021/pr501240n
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Treatment-Responsive Proteins in Different Developmental Stages of Tomato Pollen Detected by Targeted Mass Accuracy Precursor Alignment (tMAPA)

Abstract: Recently, we have developed a quantitative shotgun proteomics strategy called mass accuracy precursor alignment (MAPA). The MAPA algorithm uses high mass accuracy to bin mass-to-charge (m/z) ratios of precursor ions from LC-MS analyses, determines their intensities, and extracts a quantitative sample versus m/z ratio data alignment matrix from a multitude of samples. Here, we introduce a novel feature of this algorithm that allows the extraction and alignment of proteotypic peptide precursor ions or any other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…Furthermore, proteins of different types of HSPs (i.e. belonging to diverse families, like sHSP, HSP70, HSP90, and HSP100) accumulate in developing anthers and pollen grains after a short period of hightemperature stress (Frova et al, 1989(Frova et al, , 1991Jagadish et al, 2010;Chaturvedi et al, 2015), which points to a capacity for both tissues to activate "classical" thermotolerance mechanisms. A recent study in tomato (Solanum lycopersicum) has shown that induction of HSR protects microspores from high temperature (Fragkostefanakis et al, 2016b).…”
Section: Acclimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, proteins of different types of HSPs (i.e. belonging to diverse families, like sHSP, HSP70, HSP90, and HSP100) accumulate in developing anthers and pollen grains after a short period of hightemperature stress (Frova et al, 1989(Frova et al, , 1991Jagadish et al, 2010;Chaturvedi et al, 2015), which points to a capacity for both tissues to activate "classical" thermotolerance mechanisms. A recent study in tomato (Solanum lycopersicum) has shown that induction of HSR protects microspores from high temperature (Fragkostefanakis et al, 2016b).…”
Section: Acclimationmentioning
confidence: 99%
“…Moreover, the UPR is essential for regular pollen development, given that several mutants in the pathway have male gametophyte defective or lethal phenotypes (Fragkostefanakis et al, 2016a). During or shortly after a heat shock or longterm exposure to mild heat, the UPR is up-regulated in male reproductive tissues at transcript and protein level (Frank et al, 2009;Bita et al, 2011;Chaturvedi et al, 2015;Li et al, 2015;Fragkostefanakis et al, 2016b), suggesting the UPR has a function in acclimation of developing pollen to heat. Experimental support for this hypothesis was recently delivered, through the analysis of an ire1a ire1b double knockout mutant, which inactivates the RNA-splicing arm of the UPR signaling pathway.…”
Section: Protein Homeostasis In the Er: The Unfolded Protein Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Hazera 3017) under control and short heat stress conditions. These experiments also led to the conclusion that microspore and polarized pollen stages are crucial in the heat stress responses (Chaturvedi et al 2015). At this specific stage, they found accumulation of proteins linked with the ROS scavenger ascorbate peroxidase which is in line with the strong accumulation of flavonoid antioxidants we found in the polarized pollen stage of the cv.…”
Section: Spot-itn Converges To a Similar Result: Microsporogenesis Issupporting
confidence: 71%
“…Due to the development of robust and reproducible hyphenated techniques such as liquid-chromatography coupled to mass spectrometry label-free-shotgun proteomics has developed into a cornerstone of quantitative proteomics and phosphoproteomics studies which cannot be reviewed here in detail. However, many recent studies from our lab have provided lots of insights in proteome dynamics and adaptation strategies of various plant species and families in stress physiology, development and even field studies of crop plants (Weckwerth et al, 2004; Wienkoop et al, 2004, 2006, 2008; Morgenthal et al, 2005; Hoehenwarter et al, 2008, 2011, 2013; Weckwerth, 2008; Chen et al, 2010; Cerný et al, 2013; Chaturvedi et al, 2013, 2015, 2016; Valledor et al, 2013, 2014; Ischebeck et al, 2014; Paul et al, 2015; Ghatak et al, 2016, in press; Liu et al, 2016; Nukarinen et al, 2016; Wang et al, 2016a,b). Especially, the analysis of posttranslational modifications of proteins is an exclusive approach in proteomics and cannot be covered by any other method.…”
Section: Introductionmentioning
confidence: 99%